Gastric cancer risk after vagotomy. Issue 7 (July 1994) - Lundegårdh, G; Ekbom, A; McLaughlin, J K; Nyrén, O
Abstract : The risk of gastric cancer after vagotomy for benign gastric and duodenal disease was examined in a population based cohort of 7198 patients operated on during 1971-79 and followed up until 1988. After exclusion of the first year of follow up there were 34 cases of gastric cancer compared with 25.6 expected (standardised incidence ratio (SIR) = 1.33; 95% confidence intervals (CI) 0.92 to 1.86). Separate analyses by duration of follow up, sex, age at operation, underlying diagnosis, and operative procedures did not show any significant increased or decreased risk of gastric cancer in any of the subgroups. In conclusion, decreased gastric acid secretion after vagotomy does not increase the risk of gastric cancer in the first 10 years after operation or in the subgroup followed up for 10-18 years. A longer follow-up is needed before an excess risk can be excluded.